Toxicity across food webs: effects of karanja oil on greenhouse whitefly on tomato and two commercial biocontrol agents - Cabra-Arias, César; Carrillo, Juli (Frontiers in Insect Science, 2026)
Integrated pest management programs often incorporate insect natural enemies for biological control alongside the application of pesticides. However, pesticides can directly affect the survival and performance of beneficial predaceous insects, decreasing their efficacy. Conversely, pesticides may also increase the susceptibility of insect pests to biological control, promoting the predatory performance of their natural enemies. Pest management can be improved by understanding the ecological interaction among plants, pests, and predators, as well as the influence of pesticide application on higher trophic levels. We conducted bioassays on tomato plants (Solanum lycopersicum L.) to evaluate the effects of karanja oil, a presumed insecticidal botanical extract obtained from the seeds of the tree Pongamia pinnata L, on the greenhouse whitefly Trialeurodes vaporariorum (Westwood) and two of its natural enemies: the parasitic wasp Encarsia formosa (Gahan) and the lady beetle Delphastus catalinae (Horn). Our findings revealed a strong negative correlation between increasing concentrations of karanja oil and the survival of both adult and nymphal stages of greenhouse whiteflies. In whole plant trials, the highest concentration of karanja oil solution (5% v/v%) killed 80% of the whitefly adults and 84% of nymphs, while the lowest concentration (1.25% v/v%) killed 45% of adults and 53% of nymphs. Karanja oil also exhibited a residual negative effect on immature whiteflies and did not affect the parasitism rate of E. formosa. The direct application of karanja oil to non-pest predators and parasitoids was lethal, indicating that in integrated pest management programs for greenhouse whitefly in tomatoes, natural enemies should be introduced after the application of botanical extracts or used exclusively without pesticides.